PARENTAL EXPERIENCES IN AUTISM CHILDREARING - Mita Aprillia (JF Publisher, 2023)
This research is concerned about the experiences of parents raising children with ASD (Autism Spectrum Disorder) or commonly called autism. Autism is a disorder that most children suffer since infancy and toddlerhood. Parenting and raising children with autism compared to other normal children certainly have differences in the care, nurturing, growth, and development of these children. This research aims to find out the parenting experience of parents who have children with autism. This research used qualitative research methods, phenomenology, with interviews as the data search method. Interviews were conducted to several informants, including parents of children with ASD. The interviews were conducted online due to the Covid-19 pandemic, which requires us to minimize the intensity of physical interactions and social distancing. The research findings indicated that many parents suffered denial or shock when they recognized that their child had an autism spectrum disorder. Family and community support have a big impact in providing encouragement and acceptance for parents. The role of community and environment is very significant for children with autism and parents. In educating and caring for a child with autism, strength and patience are required. The research findings also identified that the major concerns of parents are usually about their children’s future and the acceptance of children with autism by the society.